INNOVATION IN ISLAMIC EDUCATION: EFFECTIVE STRATEGY IN FORMING NOBLE MORALS OF THE YOUNG GENERATION - Hidayati, Hanik; Munachifdlil ‘Ula, Ahmad Nilnal (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
The young generation, which is supposed to be the figure behind the nation's progress, appears with daily behavior that ignores ethics and morals. Moral education is expected to be able to contribute in overcoming these problems, with moral education expected to be one of the strategies in shaping the morals of the younger generation. This research aims to identify innovative strategies in Islamic education. The research method used is qualitative by taking location in the Kudus City area, Central Java Province. The findings of this study confirm that Islamic education innovation can be an effective solution in shaping the character and morals of the younger generation, as well as answering the challenges of the times. The implications of the results of this study provide a strong basis for continuing to encourage innovative strategies in religious education, ensuring the continued relevance and effectiveness of Islamic education in the modern context